Artificial Intelligence and Voice Modeling: Cutting-edge Technology in Music Production - Adrian BORZA (Studia Universitatis Babeş-Bolyai. Musica, 2025)
This article reports on some of the benefits that Artificial Intelligence has brought during the renaissance of AI science. It also reveals a few of the shortcomings surrounding it from 2010 until the beginning of 2025. The examples provided reflect our approaches regarding AI, motivating us to present them here briefly. The article reinforces that responsible development and integration of Artificial Intelligence in music is a priority.